Identiﬁcation of escherichia coli strains from water vending machines of Kelantan, Malaysia using 16S rRNA gene sequence analysis - Ee, Yau Tan; Mohammed Arifullah; Jan, Mei Soon (Springer Netherlands, 2016)
Water vending machines provide an alternative source of clean and safe drinking water to the consumers. However, the quality of drinking water may alter due to contamination from lack of hygienic practices and maintenance of the machines. Hence, this study was conducted to determine the microbiological quality of water from vending machines and associated contact surfaces. Seventeen water samples and 85 swab samples (nozzles, drip trays, coin slots, buttons and doors) from 3 locations in Kelantan were collected. Polymerase chain reaction amplification and 16S ribosomal ribonucleic acid (rRNA) sequencing were carried out and sequences obtained were compared against the sequences available in the National Centre for Biotechnology Information database using the basic local alignment search tool programme. Coliform counts were observed in 94.12 % of water samples, 76.47 % of nozzles and 82.35 % of drip tray swabs. Furthermore, results of 16S rRNA sequence analysis indicated that two gram-negative isolates were identified as Escherichia coli U 5/41 (Accession no. NR_024570.1) and E. coli O157:H7 EDL933 (Accession no. CP008957.1) with similarity value of 100 %, respectively. The results from this study further improve our understanding of the potential microorganisms in drinking water. Regular maintenance and cleaning of water vending machines are important to reduce bacterial growth and the presence of waterborne pathogens.